Systematic review of longitudinal studies on daily health behavior and activity of daily living among older adults - Ling-ying Wang; Ling-ying Wang; Zi-yi Hu; Hong-xiu Chen; Hong Zhu; Chun-fen Zhou; Rui-xue Zhang; Meng-lin Tang; Xiu-ying Hu (Frontiers in Public Health)
BackgroundHealth behavior, as an intervention led by nursing staff, plays a pivotal role in enhancing the health of older adults. However, existing evidence has predominantly focused on isolated aspects (e.g., smoking, alcohol consumption, diet, or exercise), with most studies being cross-sectional, thereby limiting the ability to establish causal relationships between these factors and Activities of Daily Living (ADLs). A comprehensive synthesis of longitudinal studies is required to elucidate the impact of daily health behaviors on ADLs in older adults.ObjectivesOur goal was to assess the predictive relationship between daily health behaviors and ADLs, aiming to better understand their longitudinal interplay among the older adults population.DesignThis systematic review was meticulously conducted following the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and the recommendations of the Cochrane Community.Data sourcesA thorough search was conducted using Medical Subject Headings (MeSH) terms and associated keywords in databases such as PubMed, Web of Science, Embase, China National Knowledge Infrastructure (CNKI), Chinese Technical Periodicals (VIP), and Wanfang, up to December 2024.MethodsTwo researchers independently screened the articles, and data extraction and verification were carried out for those meeting the inclusion criteria. This review systematically evaluated longitudinal studies examining the correlation between various daily health behaviors and ADL performance in older adults.Results13 longitudinal studies were included after excluding duplicates and irrelevant literature. Of these, 12 (92.3%) were deemed high quality, and 1 (7.7%) was considered low quality. Daily exercise was identified as the most influential behavior for preventing ADL disability, with adherence to a Mediterranean diet (MeDi) and moderate alcohol consumption also demonstrating protective effects. In contrast, physical inactivity, a sedentary lifestyle, and smoking were strongly linked to ADL impairment, followed by sleep duration issues, infrequent consumption of fruits and vegetables, lower frequency of soy product intake, and higher energy intake.ConclusionLongitudinal data and theoretical literature indicate that daily health behavior indicators predict independence in older adults. However, these findings should be interpreted with caution due to the inability to pool data from the included studies, which exhibited significant variations in the operationalization of the indicators and ADLs. The results highlight the clinical significance of advocating for healthy behaviors to prevent early ADL decline in older adults. Implementing these insights could lead to a substantial reduction in healthcare burdens and an extension of healthy life expectancy.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023491550, identifier CRD42023491550.